2004
DOI: 10.1029/2004jc002279
|View full text |Cite
|
Sign up to set email alerts
|

Resonant coupling of a traveling air pressure disturbance with the east Adriatic coastal waters

Abstract: [1] Exceptional sea level oscillations and strong current reversals, observed in the east Adriatic on 27 June 2003, are analyzed using available meteorological and tide-gauge measurements and numerical model results. It is shown that the variability in the atmosphere-sea system was characterized by high frequencies (0.01-0.1 min À1 ) and sea level and current amplitudes surpassing 1 m and 1 m s À1 , respectively. The event was related to the occurrence of a gravity disturbance in the atmosphere above the Adria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 22 publications
2
98
0
Order By: Relevance
“…Fontseré, 1934;Ramis and Jansà, 1983;Tintoré et al, 1988;Monserrat et al, 1991a); "marubbio" in Sicily (Colucci and Michelato, 1976;Candela et al, 1999); "milghuba" in Malta (Airy, 1878;Drago, 1999), "abiki" in Nagasaki Bay, Japan (Honda et al, 1908;Akamatsu, 1982;Hibiya and Kajiura, 1982), and "Seebär" in the Baltic Sea (Defant, 1961;Metzner et al, 2000). These waves are also documented in the Yellow Sea (Wang et al, 1987), the Adriatic Sea (Hodžić, 1979(Hodžić, /1980Orlić, 1980;Vilibić et al, 2004Vilibić et al, , 2005, the Aegean Sea (Papadopoulos, 1993), the English Channel (Douglas, 1929), the Great Lakes (Ewing et al, 1954;Donn and Ewing, 1956;Harris, 1957;Platzman, 1958Platzman, , 1965Donn, 1959;Irish, 1965), the northwestern Atlantic coast (Donn and McGuinness, 1960;Donn and Balachandran, 1969;Mercer et al, 2002), the Argentine coast (Dragani et al, 2002), and the New Zealand coast (Goring, 2003(Goring, , 2005). …”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Fontseré, 1934;Ramis and Jansà, 1983;Tintoré et al, 1988;Monserrat et al, 1991a); "marubbio" in Sicily (Colucci and Michelato, 1976;Candela et al, 1999); "milghuba" in Malta (Airy, 1878;Drago, 1999), "abiki" in Nagasaki Bay, Japan (Honda et al, 1908;Akamatsu, 1982;Hibiya and Kajiura, 1982), and "Seebär" in the Baltic Sea (Defant, 1961;Metzner et al, 2000). These waves are also documented in the Yellow Sea (Wang et al, 1987), the Adriatic Sea (Hodžić, 1979(Hodžić, /1980Orlić, 1980;Vilibić et al, 2004Vilibić et al, , 2005, the Aegean Sea (Papadopoulos, 1993), the English Channel (Douglas, 1929), the Great Lakes (Ewing et al, 1954;Donn and Ewing, 1956;Harris, 1957;Platzman, 1958Platzman, , 1965Donn, 1959;Irish, 1965), the northwestern Atlantic coast (Donn and McGuinness, 1960;Donn and Balachandran, 1969;Mercer et al, 2002), the Argentine coast (Dragani et al, 2002), and the New Zealand coast (Goring, 2003(Goring, , 2005). …”
Section: Introductionmentioning
confidence: 96%
“…Analysis of destructive meteotsunami events in the Mediterranean (Orlić, 1980;Gomis et al, 1993;Rabinovich andMonserrat, 1996, 1998;Monserrat et al, 1998;Vilibić et al, 2004Vilibić et al, , 2005Vilibić, 2005) indicated that the physical mechanisms of these events were similar to the considered event in Nagasaki Bay. Tides in the Mediterranean are small; consequently, the harbour structures are not prepared to accommodate large amplitude sea level changes associated with occasional meteotsunamis.…”
Section: Koreamentioning
confidence: 99%
See 2 more Smart Citations
“…[29] Although daily values are quite useful for the detection and description of the air-sea interaction and induced processes in the sea [e.g., Vilibić et al, 2004], the lack of significant atmospheric processes in the daily data in first 10 days of August poses a question about their usefulness for studying the cause for the bottom cold water leakage between 8 and 11 August. In summary, daily winds were quite low, whereas daily heat and water fluxes on these days were characterized by a low variability.…”
Section: Meteorological Series and Coastal Air-sea Fluxesmentioning
confidence: 99%